2017
DOI: 10.1371/journal.pone.0189248
|View full text |Cite
|
Sign up to set email alerts
|

Postural control during quiet bipedal standing in rats

Abstract: The control of bipedal posture in humans is subject to non-ideal conditions such as delayed sensation and heartbeat noise. However, the controller achieves a high level of functionality by utilizing body dynamics dexterously. In order to elucidate the neural mechanism responsible for postural control, the present study made use of an experimental setup involving rats because they have more accessible neural structures. The experimental design requires rats to stand bipedally in order to obtain a water reward p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…The PC of the body segments represents a motion element with a fixed ratio among body segments, and this motion element represents the coordination among segments. Previous studies of standing in both humans 15 and intact rats 13 showed that mainly just two PCs contribute to bipedal standing. The study that assessed the coordination of intact rats 13 also indicated that PC 1 was strongly correlated with COM movements, whereas PC 2 was correlated mainly with trunk movements.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The PC of the body segments represents a motion element with a fixed ratio among body segments, and this motion element represents the coordination among segments. Previous studies of standing in both humans 15 and intact rats 13 showed that mainly just two PCs contribute to bipedal standing. The study that assessed the coordination of intact rats 13 also indicated that PC 1 was strongly correlated with COM movements, whereas PC 2 was correlated mainly with trunk movements.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies of standing in both humans 15 and intact rats 13 showed that mainly just two PCs contribute to bipedal standing. The study that assessed the coordination of intact rats 13 also indicated that PC 1 was strongly correlated with COM movements, whereas PC 2 was correlated mainly with trunk movements. Figure 2 shows the contribution ratio (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This used in human clinical practice for the diagnosis and evaluation of postural disorders and for the assessment of instability. Statokinesiograms are shown here for the first time in rats under ecological conditions, without any restraint, unlike in other studies (23,43). In this study, postural parameters are automatically studied when an animal voluntarily immobilizes itself, which reduces the need to retrain animals subjected to a stressful model of pathology (25).…”
Section: Static Parameters: Posturologymentioning
confidence: 96%
“…Due to the joystick's low stiffness, the hold-in-center requirement approximates an inverted pendulum or stick balancing problem, in which a control policy is required to produce corrective micromovements to counter deviations from the center position (Anderson 1989;Bhounsule et al 2015;Cabrera and Milton 2002;Funato et al 2017). Consistent with this, whereas early in training trajectories exhibited rapid displacements from the center position, later in training all mice produced a clearly resolved sequence of "micromovements" that maintained the joystick within the inner radius for longer periods of time (Fig.…”
Section: Mice Learn To Hold Still Before Reaching Outmentioning
confidence: 99%